2019
DOI: 10.3389/fphys.2019.01491
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lymphocyte Composition and Functionality After Intensive Training and Exhausting Exercise in Rats

Abstract: Exhausting exercise can have a deleterious effect on the immune system. Nevertheless, the impact of exercise intensity on lymphocyte composition and functionality remains uncertain. The aim of this study was to establish the influence of intensive training on lymphoid tissues (blood, thymus, and spleen) in Wistar rats. Two intensive training programs were performed: a short program, running twice a day for 2 weeks and ending with a final exhaustion test (S-TE group), and a longer program, including two exhaust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 59 publications
10
34
1
Order By: Relevance
“…These findings are in line with previously reported results in serum 23 . We hypothesized that, as previously reported in spleen 23 , MLN could be sensitive to the repetitive stress induced by the intensive training programme, which might upregulate the glucocorticoids and adrenergic receptors 71 and this, in addition to the www.nature.com/scientificreports/ higher cortisol levels observed in similarly exercised animals 23 , may explain the higher in vitro production of IgG by MLN lymphocytes. In summary, intensive training for 5 weeks in female Wistar rats, followed or not by an additional exhaustion test, appears to have caused an overtraining condition which modified both mucosal immunity and the intestinal epithelial barrier integrity.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…These findings are in line with previously reported results in serum 23 . We hypothesized that, as previously reported in spleen 23 , MLN could be sensitive to the repetitive stress induced by the intensive training programme, which might upregulate the glucocorticoids and adrenergic receptors 71 and this, in addition to the www.nature.com/scientificreports/ higher cortisol levels observed in similarly exercised animals 23 , may explain the higher in vitro production of IgG by MLN lymphocytes. In summary, intensive training for 5 weeks in female Wistar rats, followed or not by an additional exhaustion test, appears to have caused an overtraining condition which modified both mucosal immunity and the intestinal epithelial barrier integrity.…”
Section: Discussionsupporting
confidence: 94%
“…In this case, these changes might be explained by a redistribution of lymphocytes within other lymphoid and non-lymphoid organs 25 and the lymphocyte apoptosis 64,65 induced by the release of catecholamines and glucocorticoids due to the intensive exercise stress. In this regard, a previous study in animals with a similar training program showed higher cortisol levels 23,26 .…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations